Penetapan Dispensasi Kawin Terhadap Anak di Bawah Umur Akibat Hamil Di Luar Perkawinan - Haq, Muhammad Jaul; Rosita, Dian (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2024)
The purpose of marriage is to create a happy, loving and supportive family. To achieve this, it is necessary to pay attention to the age of maturity of the bride and groom, therefore the age limit for marriage in Indonesia is regulated by law. This research aims to analyze the marriage dispensation regulations and examine the considerations of judges at the Kudus Religious Court in granting requests dispensation for minors who become pregnant outside of marriage. This research used a normative legal research method with a statutory approach. The results of the research show that the marriage age dispensation is regulated in article 7 paragraph (2) of Law Number 1 of 1974 concerning Marriage, which was later revised in article 7 paragraphs (1) and (2) of Law Number 16 of 2019 concerning Amendments to the Law -Law Number 1 of 1974 concerning Marriage, Considerations of judges at the Kudus Religious Court in granting requests for marriage dispensation in the Decree of the Kudus Religious Court Number 3/Pdt.P/2024/PA.Kds, Number 47/Pdt.P/2024/PA. Kds and Number 94/Pdt.P/2024/PA.Kds for reason of avoiding harm due to the negative stigma attached to girls who become pregnant outside of marriage, where in terms of benefits, marriage is the best solution to avoid actions that are contrary to social and religious norms.